Initial Exploration on Temporal Branch of Facial Nerve Function Preservation in Plexiform Neurofibroma Resection. Issue 6 (September 2016) - Hu, Xiaojie; Bogari, Melia; Tan, Andy; Gao, Xiaoyan; Gao, Yang; Chen, Hui; Li, Wei; Jin, Yunbo; Ma, Gang; Lin, Xiaoxi
Abstract : Background: Large temporal plexiform neurofibroma (PNF) is an irritating problem that causes facial disfigurement. Surgical resection of PNF is the only effective way to remove the tumor as well as to improve the patient's facial appearance. However, temporal branch of the facial nerve (TBFN) in the tumor is prone to be destroyed during PNF removal. Thus, TBFN palsy is the inevitable complication after surgery and might induce other malformation and dysfunction. Therefore, the aim of this study is to reconstruct a nearly normal face contour while preserving the facial nerve function. Purpose: Selective PNF removal technique was designed to protect TBFN during PNF lesions resection in our patients. Methods: From May 2011 to June 2015, the authors had 10 patients who suffered from PNF in the temporal region with facial disfigurement and underwent selective PNF removal to correct the facial disfigurement while preserving TBFN as well. Result: All patients obtained the improvement of facial appearance after surgery. The temporal PNF was removed and the TBFN function successfully maintained. Plexiform neurofibroma recurrence has not been relapsed during 6 to 49 months' follow-up. Conclusions: In our initial exploration, TBFN function maintenance and facial appearance improvement can be achieved simultaneously by using PNF-selective removal surgery technique.